The Influence of TikTok Influencers on Purchasing Decisions through Viral Marketing as an Intervening Variable in The Ruang Keramik Studio - Clara Tiara Kusuma; Theresia Dhian Kusumawati; Maria Edistianda Eka Saputri (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
The purpose of this study is to analyze the influencer of influencers on purchasing decisions through viral marketing as an intervening variabel in the Ruang Keramik Studio. This study uses quantitative method. The sampling technique used was non-probability sampling with a purposive sampling method. The sample size for this study was 100 respondents, calculated using the Lemeshow formula since the population size was unknown. Data analysis in this study utilized the SmartPLS 4.0 software with a Structural Equation Modeling – Partial Least Squares (SEM-PLS) approach. The Test results showed that TikTok influencer have a direct effect on purchasing decisions in the Ruang Keramik Studio. TikTok influencers have a direct effect on viral marketing in the Ruang Keramik Studio. Viral marketing have a direct effect on Purchase Decision in the Ruang Keramik Studio. TikTok influencer have an indirect effect on Purchase Decision, through the Viral Marketing variable as an intervening variable in the Ruang Keramik Studio (can mediate).